Game engines and machine learning (O'Reilly, 2019)
"Games are wonderful contained problem spaces, making them great places to explore AI--even if you're not a game developer. Paris Buttfield-Addison (Secret Lab Pty. Ltd.), Mars Geldard (University of Tasmania), and Tim Nugent (lonely.coffee) teach you how to use Unity to train, explore, and manipulate intelligent agents that learn. You'll train a quadruped to walk, then train it to explore, fetch, and manipulate the world. It's a little bit technical, a little bit creative. Join Paris, Mars, and Tim to learn how to use game technologies such as Unity to further your understanding of machine learning fundamentals and solve problems."--Resource description page